Vitamin Deficiencies among Adult Patients with Recurrent Aphthous Stomatitis: A Systematic Review - Anggun Rafisa; Felisha Febriane Balafif; Nuroh Najmi; Faisal Kuswandani (Sean Institute, 2025)
Recurrent aphthous stomatitis (RAS) is a common inflammatory condition of the oral mucosa characterized by recurrent, painful ulcerations that significantly impair quality of life. Although its etiology is multifactorial, nutritional factors, particularly vitamin deficiencies, have been proposed as potential contributors through their roles in immune regulation, epithelial integrity, and wound healing. Evidence regarding vitamin status in adults with RAS, however, remains inconsistent. This systematic review aimed to synthesize and critically evaluate available evidence on vitamin levels in adult patients with recurrent aphthous stomatitis. A comprehensive literature search was conducted in PubMed and Scopus for studies published between January 2015 and December 2025, following PRISMA 2020 guidelines. Eligible studies included adult participants (≥18 years) diagnosed with RAS and reported serum or salivary vitamin levels. Observational and interventional studies were considered. Data were extracted on study characteristics, vitamin assessment methods, and key findings, and were analyzed descriptively. Seven studies met the inclusion criteria. Vitamin D was the most frequently investigated micronutrient, followed by vitamin B12 and other hematinic parameters. Several studies reported lower vitamin D levels in patients with RAS compared with controls, while others found similarly high rates of deficiency in both groups. Associations between vitamin levels and clinical severity of RAS were generally weak, although vitamin D deficiency was linked to increased ulcer multiplicity in one study. Vitamin B12 deficiency was primarily observed in populations with concomitant iron deficiency anemia rather than in otherwise healthy adults with RAS. Current evidence suggests that vitamin deficiencies, particularly vitamin D, may function as modifying or aggravating factors in adult RAS rather than direct causal agents. Further high-quality studies are required to clarify their clinical relevance and therapeutic implications.